2016
DOI: 10.5194/acp-16-6071-2016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the anthropogenic heat flux and its effect on regional meteorology and air quality over the Yangtze River Delta region, China

Abstract: Abstract. Anthropogenic heat (AH) emissions from human activities caused by urbanization can affect the city environment. Based on the energy consumption and the gridded demographic data, the spatial distribution of AH emission over the Yangtze River Delta (YRD) region is estimated. Meanwhile, a new method for the AH parameterization is developed in the WRF/Chem model, which incorporates the gridded AH emission data with the seasonal and diurnal variations into the simulations. By running this upgraded WRF/Che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
94
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 52 publications
10
94
1
5
Order By: Relevance
“…It was reported that the typical values of AH fluxes in urban areas range from 20 to 100 W m −2 (Crutzen, 2004;Sailor and Lu, 2004;Fan and Sailor, 2005;Pigeon et al, 2007;Lee et al, 2009;Iamarino et al, 2012;Lu et al, 2016;Xie et al, 2016). Sometimes, the fluxes might exceed the value of 100 W m −2 (Iamarino et al, 2012;Quah and Roth, 2012;Lu et al, 2016;Xie et al, 2016), with the extreme value of 1590 W m −2 in the densest part of Tokyo at the peak of air-conditioning demand (Ichinose et al, 1999).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that the typical values of AH fluxes in urban areas range from 20 to 100 W m −2 (Crutzen, 2004;Sailor and Lu, 2004;Fan and Sailor, 2005;Pigeon et al, 2007;Lee et al, 2009;Iamarino et al, 2012;Lu et al, 2016;Xie et al, 2016). Sometimes, the fluxes might exceed the value of 100 W m −2 (Iamarino et al, 2012;Quah and Roth, 2012;Lu et al, 2016;Xie et al, 2016), with the extreme value of 1590 W m −2 in the densest part of Tokyo at the peak of air-conditioning demand (Ichinose et al, 1999).…”
mentioning
confidence: 99%
“…surfaces to artificial ones (Civerolo et al, 2007;Lo et al, 2007;Wang et al, 2007;Jiang et al, 2008;Lu et al, 2010;Wu et al, 2011;Chen et al, 2014b;Liao et al, 2015;Zhu et al, 2015;Li et al, 2016) and the release of anthropogenic heat from human activities in cities (Ryu et al, 2013;Yu et al, 2014;Xie et al, 2016). Anthropogenic heat (AH) can increase turbulent fluxes in sensible and latent heat (Oke, 1988), implying that it can modulate local and regional meteorological processes (Ichinose et al, 1999;Block et al, 2004;Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Feng et al, 2012Feng et al, , 2014Menberg et al, 2013;Ryu et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Chen et al, 2014a;Meng et al, 2011;Yu et al, 2014;Xie et al, 2016) and thereby exert an important influence on the formation and the distribution of ozone (Ryu et al, 2013;Yu et al, 2014;Xie et al, 2016) as well as aerosols (Yu et al, 2014;Xie et al, 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The redistribution of primary and secondary pollutants between the surface and the upper levels of the atmosphere also plays a crucial role. According to [11], this phenomenon, together with the increase in temperature, results in an increase in surface ozone concentrations in urban areas with a maximum of 2.5 ppb in winter and 4 ppb in summer. The authors of [12] show that on average, daytime ozone concentrations decrease by about 2 ppbv in the lower boundary layer, while they increase by about 40 ppbv in the upper levels in a city downwind of Shanghai.…”
Section: Introductionmentioning
confidence: 99%